APLIKASI SISTEM PENGAMBILAN KEPUTUSAN DALAM MANAJEMEN RANTAI PASOK MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN BALANCE SCORECARD (BSC) BERBASIS WEBSITE - Widiyastuti Widiyastuti; Jemmy Edwin Bororing; Fatsyahrina Fitriastuti (Informasi Interaktif, 2020)
The supply chain concept is a new concept in implementing an integrated logistics system. This concept is a supply chain of goods from raw materials to finished goods (indrajit and Djokopranoto 2002). Supply chain management (MRP) of agricultural products represents the management of the entire production process as a whole from processing, distribution, marketing, to the desired product reaching consumers. Thus, the Supply Chain Management System can be defined as a unified integrated marketing system, which includes the integration of products and actors, in order to provide customer satisfaction. This study aims to design a decision-making system application in supply chain management using the AHP and BSC methods. This application can provide convenience to the farmer's blessing cooperative in Tawangmangu Karanganyar in the product purchase transaction process. In addition to providing convenience to the cooperative, it can also provide other advantages, namely not destroying market prices, so as not to harm the farmers. In the design process, this application can be used by two users, namely the admin side who has full rights in managing the system. And the user who can update product data, can find out product information, product stock and others. Based on the results of the design, implementation and testing of this application, it can provide solutions to farmers, buyers and cooperatives in implementing MRP (Management Supply Chain). In the results of trials on users, the test results of this application provide information sufficient, simple appearance, easy to use and can provide convenience to users and cooperatives in the transaction process.. Keywords: Supply Chain Management, AHP, BSC, Decision Support Systems.